Focal Epileptiform Discharges Can Mimic Electrode Artifacts When Recorded on the Scalp Near a Skull Defect - Edward C. Mader MD; Daniella Miller MD, MPH; Jeremy M. Toler MD; Piotr W. Olejniczak MD, PhD (SAGE Publishing, 2018)
Breach rhythm, the hallmark of skull defect, is a familiar finding in the electroencephalogram (EEG). A hole in the skull can also give rise to unfamiliar EEG findings. We present 3 patients with a skull defect whose scalp EEG showed focal epileptiform discharges that resembled F4 electrode artifacts-a 23-year-old man with a right-sided craniectomy for traumatic brain injury, a 63-year-old woman with a history of bifrontal craniectomy and meningioma resection, and a 77-year-old woman who had a right hemicraniectomy for a life-threatening subdural hematoma. In all 3 patients, the F4 electrode was directly above or near a skull defect, and scalp EEG showed phase-reversing waves in FP2-F4 and F4-C4 with no clear-cut "physiological field" (even when the EEG was displayed at a higher sensitivity). In the first 2 patients, the technologist tried to eliminate the "electrode artifacts" by cleaning the scalp thoroughly, replacing the F4 electrode, and maintaining electrode impedance between 2 and 5 kΩ. These measures failed to eliminate the "electrode artifacts" so the EEG was recorded from four 10-10 electrode sites around F4. Extending the montage made it clear that what appeared as F4 electrode artifacts were actually focal epileptiform discharges. Correlation with other electroclinical and neuroimaging data was enough to resolve this issue in the third patient, obviating the need to extend the montage. When recording and interpreting the EEG of patients with a craniotomy or craniectomy, EEG professionals should be aware that focal epileptiform discharges can masquerade as electrode artifacts.